2020
DOI: 10.1210/clinem/dgaa795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Consequences of C-Terminal Variants in MCT8: A Case Series

Abstract: Context Genetic variants in SLC16A2, encoding the thyroid hormone transporter MCT8, can cause intellectual and motor disability and abnormal serum thyroid function tests, known as MCT8 deficiency. The C-terminal domain of MCT8 is poorly conserved, which complicates predicting the deleteriousness of variants in this region. We studied the functional consequences of five novel variants within this domain and their relation to the clinical phenotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…MCT8 Deficiency: From Pathophysiology to Therapy phenotype (59). Additional studies are warranted to further delineate the relationship between the different mutations and the phenotypic variability.…”
Section: Disease Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCT8 Deficiency: From Pathophysiology to Therapy phenotype (59). Additional studies are warranted to further delineate the relationship between the different mutations and the phenotypic variability.…”
Section: Disease Characteristicsmentioning
confidence: 99%
“…Evaluation of residual thyroid hormone transport capacity of these variants in in vitro systems or patient-derived fibroblasts is therefore indispensable to confirm the pathogenic nature of identified variants ( 56 58 ). Recent studies suggested that C-terminal missense variants beyond amino acid residue Met574 (long isoform) are well-tolerated and likely to not results in a phenotype ( 59 ). Additional studies are warranted to further delineate the relationship between the different mutations and the phenotypic variability.…”
Section: Disease Characteristicsmentioning
confidence: 99%
“…The thyroid profile in our patient is consistent with the literature. More than 80 different mutations of SLC16A2 gene have been described from over 100 families to date (9). The identified mutations of the SLC16A2 gene include causing splice site mutations, deletions or insertions of one or more codons, nonsense mutations causing a premature truncation of the MCT8 protein and missense mutations leading to 1-amino-acid substitutions (10).…”
Section: Introductionmentioning
confidence: 99%